2018
DOI: 10.17691/stm2018.10.4.21
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Technology in Complex Medical Rehabilitation of Patients with Disabilities (Review)

Abstract: The review is devoted to integration of innovative virtual reality technologies in the complex of medical rehabilitation of patients with disabilities. The analysis of data presented in modern domestic and foreign literature proves the effectiveness of using these technologies for recovery of impaired motor functions in patients of various ages with nervous and musculoskeletal system pathologies and gives evidence of their corrective effect on neurophysiological motor deficiency. Evaluation of the achieved res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In a review of the application of Virtual Reality in Complex Medical Rehabilitation, it was concluded that "the use of virtual environments has proven effective for the recovery of impaired motor skills in people with disabilities". Nevertheless, it is necessary to provide personalized scenarios, goals, and tasks in order to achieve the maximum possible improvement in physical and cognitive skills as well as to register the results obtained during the sessions for each user [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the application of Virtual Reality in Complex Medical Rehabilitation, it was concluded that "the use of virtual environments has proven effective for the recovery of impaired motor skills in people with disabilities". Nevertheless, it is necessary to provide personalized scenarios, goals, and tasks in order to achieve the maximum possible improvement in physical and cognitive skills as well as to register the results obtained during the sessions for each user [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a review about the application of Virtual Reality in Complex Medical Rehabilitation, authors once analyzed the literature and concluded that the use of virtual environments has proven effectiveness on the recovery of impaired motor skills in people with disabilities. However, to get the optimal results of this application, a personalized approach and monitoring registration of some physical and cognitive variables are required [6].…”
Section: Discussionmentioning
confidence: 99%
“…2) Situational cognitive theory Situational learning emphasizes the critical role of students' interaction with the environment and practice in the learning process. The theory holds that meaningful knowledge construction can only occur in the learning process combined with real situations [17]. VR technology provides a virtual immersive learning situation so that students have a "sense of presence."…”
Section: ) Constructivismmentioning
confidence: 99%